Diagnostic performance of noninvasive imaging modalities for localization of insulinoma: A meta-analysis. Issue 145 (December 2021) - Yang, Yi; Shi, Jian; Zhu, Jianbing
Highlights: This was a meta-analysis to compare imaging modalities for insulinoma localization. PET/CT showed superior performance than SPECT/CT, CT and MRI. GLP-1R based PET/CT manifested better diagnostic performance. Abstract: Background: Insulinoma is the most common functional neuroendocrine tumor found only in the pancreas. The early detection of insulinoma is of importance. Studies comparing the performance of noninvasive modalities were limited by sample size and heterogeneity between studies. The aim of this meta-analysis was to evaluate the diagnostic performance of PET/CT, SPECT/CT, CT and MRI for the localization of insulinoma, and to provide evidence for clinical practice. Methods: PubMed, Embase, Cochrane Library, Wanfang Data and China National Knowledge Infrastructure were searched from inception to May 31, 2021. Pooled sensitivity, specificity, positive Likelihood Ratio (+LR) and negative Likelihood Ratio (−LR), diagnostic odds ratio (DOR), and concordance rate were calculated. Results: A total of 19 studies including 708 patients of insulinoma reached the inclusion criteria. PET/CT imaging demonstrated a pooled sensitivity of 0.79 (95% CI: 0.54–0.92) and a pooled specificity of 0.84 (95% CI: 0.20–0.99). The pooled sensitivity and specificity of SPECT/CT were 0.77 (95% CI: 0.46–0.93) and 0.45 (95% CI: 0.22–0.70). CT showed an overall sensitivity of 0.54 (95% CI: 0.35–0.72) and specificity of 0.75 (95% CI: 0.54–0.88). The pooled sensitivity and specificity for MRI were 0.54 (95% CI: 0.31–0.75) and 0.65 (95% CI: 0.39–0.84), respectively. The concordance rates of PET, SPECT, CT, and MRI were 78% (95% CI: 66–90%), 74% (95% CI: 52–97%), 56% (95% CI: 41–72%), and 53% (95% CI: 33–73%), respectively. Conclusion: Results of this study indicate that PET/CT demonstrated superior performance than SPECT/CT, CT and MRI for the localization of insulinoma. GLP-1R based PET/CT manifested better diagnostic performance in comparison with SSTR based PET/CT imaging modality.